Realne koalicje w Sejmie w roku 2004 - Hausner, Jerzy; Sokołowski, Andrzej (Cluster analysis of the legislative activity of Sejm in 2004, 2006)
For this reasearch 241 statutes passed by Sejm in 2004 have been considered. The quantitative data consists of the information on the number of votes provided by each parliamentary club in terms of four classes: yes, no, obstained, not voting. Deputies' clubs gather members of the Chamber representing similar political views, usually members of the same party or political group who for some reason decided to act jointly. According to the rules of procedure of the Sejm, a club can be founded by at least 15 Deputies. The following clubs active throughout the whole year of 2004 have been taken into account: Democratic Left Alliance, Civic Platform, Law and Justice, Polish People’s Party, Self-defence of the Republic of Poland, League of Polish Families, Union of Labour and also a group of Non affiliated deputies. The data has been transformed into percentage structures, separately for each club, thus the classification space has been created. The number of homogeneous groups of statutes have been obtained by the analysis of dendrogram produced by the agglomerative Ward’s clustering method. The final classification was done by k-means method. Six groups of statutes have been analysed from the point of view of their subject, and the behaviour of parliamentary clubs. The authors have found the real alliances being observed in Sejm in 2004 while passing statutes of different kinds.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 27-36